Far Infrared Modulated Photoluminescence (FIRM-PL) study of a 2-D electron gas in GaAs/AlxGa1-xAs heterojunctions and quantum wells - Nicholas, R; Chang, C; Zhitomirskiy, V (2000)
The new technique of Far InfraRed Modulated PhotoLuminescence (FIRM-PL) has been used to study the properties of a high mobility 2-D electron gas in a series of GaAs/AlGaAs heterojunctions and quantum wells. When the occupancy of the lowest Landau level is between 1 and 2 very large transfers of PL intensity are observed at the cyclotron resonance condition. The FL intensity is transferred from the E-0 line to F-1 corresponding to emission from the first two quantised electric subbands. A study of the power dependence of this signal allows us to deduce that the relative recombination efficiencies of the two lines are around 5 orders of magnitude different in such structures. This difference leads to a very high sensitivity for this technique for the observation of internal excitations within the electron system. In quantum wells signals are seen for all occupancies due to transfer between PL from higher Landau levels.